New emerging results on molecular gas, stars, and dust at z ~ 2, as revealed by low star formation rate and low stellar mass star-forming galaxies. Issue Volume 11:Issue S319(2015) (17th August 2016) - Dessauges-Zavadsky, Miroslava; Zamojski, Michel; Schaerer, Daniel; Combes, Françoise; Egami, Eiichi; Sklias, Panos; Swinbank, Mark A.; Richard, Johan; Rawle, Tim
Abstract: Recent CO surveys of star-forming galaxies (SFGs) at z ~ 2 have revolutionized our picture of massive galaxies. It is time to expand these studies toward the more common z ~ 2 SFGs with SFR < 40 M ⊙ yr −1 and M * < 2.5 × 10 10 M⊙ . We have derived molecular gas, stars, and dust in 8 such lensed SFGs. They extend the L IR – L 'CO(1-0) distribution of massive z >1 SFGs and increase the spread of the SFG star formation efficiency (SFE). A single star formation relation is found when combining all existing CO-detected galaxies. Our low- M * SFGs also reveal a SFE decrease with M * as found locally. A rise of the molecular gas fraction ( f gas ) with redshift is observed up to z ~ 1.6, but it severely flattens toward higher redshifts. We provide the first insight into the f gas upturn at the low- M * end 10 9.4 < M * /M⊙ < 10 10 reaching f gas ~ 0.7, it is followed by a f gas decrease toward higher M * . Finally, we find a non-universal dust-to-gas ratio among local and high-redshift SFGs and starbursts with near-solar metallicities.